Longitudinal changes in plasma Caspase-1 and Caspase-3 during the first 2 years of HIV-1 infection in CD4Low and CD4High patient groups. - Jingjing Song; Yanmei Jiao; Tong Zhang; Yonghong Zhang; Xiaojie Huang; Hongjun Li; Hao Wu (PLoS ONE, 2015)
Over 95% of CD4 cell death occurs by Caspase-1-mediated pyroptosis during HIV infection. Caspase-3-mediated apoptosis accounts for the death in a small proportion of infected CD4 cells. To date, there have been no reports on the dynamics of Caspase-1 and Caspase-3 and their relationship with disease progression in acute HIV-1 infection. In this study, two distinct HIV-1 patient groups were enrolled. The CD4High group maintained a CD4 level above 450 cells/μl while CD4 levels in the CD4Low group dropped below 250 cells/μl within 2 years after infection. Blood samples were collected at 1, 2, 3, 4, 6, 12 and 24 months after HIV infection. Plasma Caspase-1 and Caspase-3 levels in the two patients groups were determined by a single-step ELISA using commercially available monoclonal antibodies. The results showed that Caspase-1 and Caspase-3 levels in the CD4High group increased rapidly and then decreased within a short time during early HIV-1 infection. In contrast, Caspase-1 and Caspase-3 levels in the CD4Low group were obviously increased after 1 year of HIV-1 infection.